Entre destructions et reconstructions, le patrimoine sicilien pendant et après la Seconde Guerre mondiale - Giovanni Polizzi; Samuel Romeo (Frontière·s)
In this contribution we present the traces, on the field and within the archive, of a bombing that took place in Solunto on the night of December 12, 1942. The starting point for this research was a photograph preserved in the archives of the Antonio Salinas Regional Archaeological Museum, documenting the restoration of a cistern in Solunto following the Allied bombings. Archival research made it possible to reconstruct the chronology of the facts and to reveal the commitment of the Superintendents of Antiquities of Western Sicily, Jole Bovio Marconi and Vincenzo Tusa, during and after the war to protect the cultural heritage. Solunto, like many other Sicilian localities, was a strategic sites that hosted Italian-German military garrisons. The events of the Second World War are here analyzed from the point of view of sensitivity to the cultural heritage, its perception during conflicts and during periods of peace. We will explore the attempts to protect the cultural heritage and the phases of restoration and consolidation that took place from the war up to the long archaeological excavations directed by Vincenzo Tusa, of which we can now see the fruits walking through the ruins of Solunto.